Modelo hidrosanitario para una vivienda autosostenible de dos plantas en el Municipio de la Vega, Cundinamarca (2021)
The collection of rainwater for consumption and domestic uses represents an interesting practice, both economically for the consumer and environmentally for the planet. This article presents a proposal for the use of rainwater and gray water recirculation for a two-story house in the municipality of La Vega, Cundinamarca. Important aspects were developed such as search for alternatives for hydrosanitary facilities and water recirculation, preparation of a state of knowledge in accordance with the review of the literature and applicable current regulations.